PBF509, an Adenosine A2A Receptor Antagonist With Efficacy in Rodent Models of Movement Disorders - Núñez, Fabiana; Taura, Jaume; Camacho, Juan; López-Cano, Marc; Fernández-Dueñas, Víctor; Castro, Naomi; Castro, Julio; Ciruela, Francisco (Frontiers in Pharmacology, 2018)
Adenosine A2A receptor (A2AR) antagonists have emerged as complementary non-dopaminergic drugs to alleviate Parkinson’s disease (PD) symptomatology. Here, we characterize a novel non-xhantine non-furan A2AR antagonist, PBF509, as a potential pro-dopaminergic drug for PD management. First, PBF509 was shown to be a highly potent ligand at the human A2AR, since it antagonized A2AR agonist-mediated cAMP accumulation and impedance responses with KB values of 72.8 ± 17.4 and 8.2 ± 4.2 nM, respectively. Notably, these results validated our new A2AR-based label-free assay as a robust and sensitive approach to characterize A2AR ligands. Next, we evaluated the efficacy of PBF509 reversing motor impairments in several rat models of movement disorders, including catalepsy, tremor, and hemiparkinsonism. Thus, PBF509 (orally) antagonized haloperidol-mediated catalepsy, reduced pilocarpine-induced tremulous jaw movements and potentiated the number of contralateral rotations induced by L-3,4-dihydroxyphenylalanine (L-DOPA) in unilaterally 6-OHDA-lesioned rats. Moreover, PBF509 (3 mg/kg) inhibited L-DOPA-induced dyskinesia (LID), showing not only its efficacy on reversing parkinsonian motor impairments but also acting as antidyskinetic agent. Overall, here we describe a new orally selective A2AR antagonist with potential utility for PD treatment, and for some of the side effects associated to the current pharmacotherapy (i.e., dyskinesia).